The Constitutionalization of the Civil State The Self-Definition of Egypt, Tunisia and Yemen Following the Arab Uprisings - Lavie, Limor (2021)
This paper offers a contextualized analysis of the way in which three Islamic constitutions—in Egypt (2014/2019), Tunisia (2014), and Yemen (2015)—came to a similar self-declaration of a “civil state” (dawla madaniyya), following the Arab uprisings. This self-expressive proclamation, which did not exist in their former constitutions, nor in any other constitution worldwide, is the product of the ongoing internal struggles of Muslim societies over the definition of their collectivity between conservatism and modernity, religiosity and secularism. In Egypt, the self-definition of a civil state enshrines the one-sided narrative of the June 2013 coup regime and the Armed Forces’ intrusive move into the field of state-religion relations; in Tunisia, the constitutionalization of the civil state reflects a settlement between Islamists and non-Islamists regarding the role of Islam in politics and legislation; in Yemen, it expresses an aspiration of detribalization and modernization within an Islamic model of statehood. The paper further seeks to trace the path of migration of this idea from one country to another, and the interconnectedness between the three cases, while pointing out possible implications on future constitution making in other Muslim countries.
Keywords: Arab Spring; Egypt; Islam; Tunisia; Yemen; civil state; Constitutions; Modernity; Religion; Secularism; Tribalism